Legal Attitudes of Immigrant Detainees. Issue 1 (March 2017) - Ryo, Emily
Abstract : A substantial body of research shows that people's legal attitudes can have wide‐ranging behavioral consequences. In this article, I use original survey data to examine long‐term immigrant detainees' legal attitudes. I find that the majority of detainees express a felt obligation to obey the law, and do so at a significantly higher rate than other U.S. sample populations. I also find that the detainees' perceived obligation to obey U.S. immigration authorities is significantly related to their evaluations of procedural justice, as measured by their assessments of fair treatment while in detention. This finding remains robust controlling for a variety of instrumental and detainee background factors, including the detainees' experiences with the legal system and legal authorities in their countries of origin. Finally, I find that vicarious procedural justice evaluations based on detainees' assessments of how others are treated are as important to detainees' perceived obligation to obey U.S. immigration authorities as their personal experiences of fair or unfair treatment. I discuss the broader implications of these findings and their contributions to research on procedural justice and legal compliance, and research on legal attitudes of noncitizens.